A 3-D mechanics-based particle shape index for granular materials. (September 2018) - Kawamoto, Reid; Andrade, José; Matsushima, Takashi
Highlights: Mechanics-based particle shape index developed for 3-D. Relationships between shape index, particle rotations, and average stress. Simple micromechanical model to provide possible explanation for trends. Abstract: Particle shape plays an important role in the mechanical properties of granular materials. This paper studies the effect it has on particle rotations and stress via a mechanics-based 3-D particle shape index, which is based on an earlier 2-D particle shape index. A level set discrete element method (LS-DEM) simulation, with experimental validation, of a specimen of a natural sand with varying particle shapes, subject to triaxial compression, is analyzed. We show that particles whose shapes allow for more moment transmission—as characterized by the particle shape index—experience less deviation in rotation and contribute more to the macroscopic shear stress, and provide possible micromechanical explanations of these trends. The results have implications in the construction of micromechanics-based granular models and higher-order continuum models.